Aspectos celulares da cicatrização Cellular aspects of wound healing - Ricardo José de Mendonça; Joaquim Coutinho-Netto (Sociedade Brasileira de Dermatologia, 2009)
O processo cicatricial compreende uma sequência de eventos moleculares e celulares que interagem para que ocorra a restauração do tecido lesado. Desde o extravasamento de plasma, com a coagulação e agregação plaquetária até a reepitelização e remodelagem do tecido lesado o organismo age tentando restaurar a funcionalidade tecidual. Assim, este trabalho abrange os diversos aspectos celulares envolvidos no processo cicatricial, bem como os principais medicamentos utilizados no tratamento de patologias relacionadas às deficiências na cicatrização. São abordados também, os aspectos econômicos referentes, sobretudo, às feridas crônicas de pés diabéticos. Wound healing is a dynamic interactive process that involves a sequence of molecular and cellular events. Recent advances in cellular and molecular biology have greatly expanded our understanding of the biological process involved in wound repair and tissue regeneration. From plasma extravasation, with coagulation and platelet aggregation, to reepithelialization and remodeling of injured tissue, the organism acts by trying to restore functionality tissue. Thus, the present study encompasses several cellular aspects involved in the wound healing process, as well as the main drugs used in treating the pathology related to wound healing complications. Economic aspects are also addressed, mainly related to chronic wounds of diabetic feet.